Analisis Branding Hotel Swiss-Belinn Saripetojo Dengan Menggunakan Media Sosial Instagram - Gabriella Widia Devi (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
In the midst of the Covid-19 pandemic, it has had a lot of negative effects on various companies. Especially to companies engaged in hospitality services, or to companies that provide services to the community, this of course has a very significant effect on branding and also the number of visitors who come. Branding is very necessary in the conditions we are experiencing, in order to maintain public trust and to always use the services we provide. Carrying out branding activities using Instagram social media is certainly a solution, so that we are able to reach the audience by presenting some content that is conveyed easily, with the existence of social media, and is equipped with various kinds of supporting features, of course making it easier for a number of companies who is engaged in services as the Swiss-Belinn Saripetojo Hotel does.